Interactive Video Using Moovly to Train Students' Critical Thinking Skills on Plant Metabolism Material - Fitria; Ismul Mauludin Al Habib; Hanif Rafika Putri (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Students’ critical thinking skills in plant metabolism, particularly in the topic of respiration, remain relatively low. This condition is further exacerbated by low learning motivation, limited instructional media, and the use of less varied teaching methods and learning models. This study aims to analyze the effectiveness of Moovly-based interactive video media in improving students’ critical thinking skills in plant metabolism learning. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects comprised ten twelfth-grade students who participated in the trial implementation. Data were collected through expert validation, critical thinking tests (pretest–posttest), and interviews. The instruments included validation sheets, test items, and interview guidelines. Data analysis was conducted using descriptive quantitative and qualitative methods. The results indicate a significant improvement in students’ critical thinking skills after the use of the developed media. In addition, the interactive video media were rated as highly feasible based on expert evaluations. Therefore, it can be concluded that Moovly-based interactive video media are effective in enhancing students’ critical thinking skills in biology learning. This study implies the importance of utilizing interactive media as an alternative innovative instructional strategy to support higher-order thinking skills.